Quantified Self as Epistemological Anarchism. - Chiodo, Simona (Philosophia, 2022)
The phenomenon of the quantified self, which is especially addressed by sociology and medical humanities, is still quite disregarded by philosophy. Yet, the philosophical issues it raises are various and meaningful, from the realm of epistemology to the realm of ethics. Moreover, it may be read as a key symptom to investigate the complex technological era in which we live, starting from the meaning of contemporary technology itself from a philosophical perspective. I shall focus on one of the epistemological issues raised by the phenomenon of the quantified self by arguing that it may be read in terms of epistemological anarchism, which also leads to other epistemological issues, such as a possibly detectable crisis of the notions of knowledge in general and science in particular as founded on the relationship between particularity and universality, as well as between reality and ideality. I shall select cases that are peculiarly representative of the founding epistemological stance I shall focus on. Yet, the reason why they deserve special attention is that they are also representative of an increasingly widespread attitude characterising not only the community of the quantified self but also, at least to some extent, anyone of us who may happen to use technologies (from apps to self-track symptoms to google to search symptoms) to try to self-diagnose.